Illustrated basketball dictionary for young people - Clark, Steve 1947-; Baginski, Frank (New York Harvey House, 1977)
Defines basketball terminology and profiles some of basketball's greatest players.
Keywords: Basketball -- Dictionaries, Juvenile; Basketball -- Dictionaries